Conflicting incentives in the management of 529 plans - Justin Balthrop; Gjergji Cici (University of Cologne, Centre for Financial Research (CFR), 2022)
Section 529 plans have experienced tremendous growth, yet we know little about how the incentives of their sponsors (i.e., states) and program managers affect investors. We study how the incentives of these key players relate to plan characteristics. Plans where states exhibit a greater tendency to extract revenue offer investment menus with higher underlying fees, weaker performance, and limited options. In addition, their sponsors offer no other direct or indirect benefits that offset these plans' inferior investment menus. Our evidence suggests conflicts of interest faced by program managers and lack of investment sophistication of sponsoring states as likely explanations.
Keywords: 330; 529 plans; conflicts of interest; plan sponsor; program manager; revenue sharing